Programming multi-agent systems : 8th International workshop, ProMAS 2010, Toronto, ON, Canada, May 11, 2010. Revised Selected Papers - Dix, Jurgen; Novák, Peter; Collier, Rem (Lecture Notes in Computer Science, 2012)
This book constitutes the proceedings of the 8th International Workshop on Programming Multi-Agent Systems held in Toronto, Canada, in May 2010 in conjunction with AAMAS 2010, the 9th International Joint Conference on Autonomous Agents and Multiagent Systems. The 7 revised full papers presented together with 1 invited paper were carefully reviewed and selected for inclusion in the book. The papers cover a broad range of mostly practical topics like decision component of agent systems; practical examples of programming languages; interaction with the environment, and are thus organized in topical sections on reasoning, programming languages, and environments.